Olfactory Objects - Carvalho, Felipe (2016)
The philosophy of perception has been mostly focused on vision, to the detriment of other modalities like audition or olfaction. In this paper I focus on olfaction and olfactory experience, and raise the following questions: is olfaction a perceptual-representational modality? If so, what does it represent? My goal in the paper is, firstly, to provide an affirmative answer to the first question, and secondly, to argue that olfaction represents odors in the form of olfactory objects, to which olfactory qualities are attributed. In order to do this I develop an empirically adequate notion of olfactory object that is sensitive to the peculiarities of olfaction, and defend it against various objections.